A dual response fluorescent sensor for HNO and S2− ions using a Cu(ii) complex based probe assisted by detailed DFT studies. Issue 33 (7th August 2018) - Dutta, Ananya; Alam, Rabiul; Islam, Abu Saleh Musha; Dutta, Arpan; Ali, Mahammad
Abstract : A Cu(ii ) based sensor for selective detection of HNO and S 2− with detailed DFT studies is reported here. Abstract : A Cu(ii ) based sensor (1 ) prepared by the complexation between (quinolin-8-ylamino)-acetic acid hydrazide (L 2 ) and Cu 2+ ions has been developed for a highly sensitive and selective recognition of HNO and S 2− over other biologically abundant anions with prominent enhancement in absorption and emission intensities. The sensor (1 ) shows weak fluorescence due to ET (electron transfer) but upon addition of HNO and S 2− a large enhancement in the fluorescence intensity (F.I.) was observed over other possible competitive anions on the basis of reduction of Cu(ii ) to Cu(i ) and formation of CuS, respectively. The 1 : 1 complexation was characterized by mass spectrometry (MS), elemental analysis and Job's plot. The corresponding K f value was evaluated to be (4.934 ± 0.05) × 10 4 M −1 for Cu 2+ from UV-Vis absorption titration. Quantum yields ofL 2 and [Cu-L 2 + S 2− ] and [Cu-L 2 + HNO] complexes in acetonitrile (CH3 CN) are found to be 0.107, 0.09 and 0.07, respectively, using quinine sulphate as the standard.